Management of reduced fetal movement: A comparative analysis of two audits at a tertiary care clinical service. (May 2020) - Kapaya, Habiba; Almeida, Joana; Karouni, Faris; Anumba, Dilly
Abstract: Objectives: Reduced fetal movement (RFM) is a commonly presenting worrisome complaint, both for mothers and attending clinicians. The aim of this study was to review the management of RFM before and following the implementation of new hospital guideline and to determine pregnancy outcomes following single vs repeated consultations with complaints of RFM. We also compared the standards in our old and new trust guidelines against published guidance from the Royal College of Obstetricians and Gynaecologists (RCOG). Study Design: This retrospective cohort study was conducted between June -November 2016 (audit 1) and July– December 2018 (audit 2). All women with a non-anomalous singleton pregnancy, attending the Day Assessment Unit of the Jessop Wing Hospital Sheffield UK with a primary presentation of perceived RFM after 24 weeks of gestation were included. The electronic maternity database was used to collect information regarding their presentations and pregnancy outcomes. Adherence to the old and the new local guidelines for the respective epochs of the assessment were reviewed by two independent observers using the Appraisal of Guidelines for Research and Evaluation (AGREE) 11 tool. Results: A total of 1775 women presented with RFM during the two study periods. Of these, 632 attended with more than 1 presentation of RFM (35.6 %). There were 3 stillbirths; all diagnosed at the first presentation with RFM. In the second audit, prevalence of RFM increased by 10 %, CTG documentation improved by 1% and ultrasound scan requests decreased by 6.6 %. Women with more than one episode of RFM were more likely to be younger, smokers, nulliparous, have raised BMI, had a higher IOL rate and had more ultrasound scans compared to those with one episode. However, neonatal outcome, onset of labour and mode of delivery remained unchanged between the two groups. While the RCOG guideline was superior to both (old and new) guidelines, the overall scores increased in the new guideline by 22 %. Conclusion: After implementing the new guideline, the re-audit demonstrates a reduction in the number of requested ultrasound scans without any compromise on the perinatal outcome.